1999
DOI: 10.1111/j.1600-0714.1999.tb02053.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated production of salivary nitric oxide in oral mucosal diseases

Abstract: Nitric oxide (NO) is known to play an important role in biological systems. In this study, we measured levels of NO in the saliva of 39 patients with oral mucosal diseases: 21 had oral lichen planus (OLP) and 18 had recurrent aphthous ulceration (RAU). NO was assayed using the Griess reagent, which measures nitrite (NO2), the byproduct of NO. NO2 was detected in all tested samples, and levels in the saliva of patients were significantly increased relative to those of healthy subjects. We also examined the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 27 publications
5
58
1
2
Order By: Relevance
“…It was suggested that the serum NO level is elevated in megaloblastic anemia [42] and that the plasma NO level in betathalassemia minor patients is low at the time of diagnosis [43]. In addition, excessive salivary NO plays a potential role in modifying oral mucosal diseases, as a physiopathological regulator [44]. Many recent studies have reported increased NO production in Table 3 certain temporomandibular disorders [5].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the serum NO level is elevated in megaloblastic anemia [42] and that the plasma NO level in betathalassemia minor patients is low at the time of diagnosis [43]. In addition, excessive salivary NO plays a potential role in modifying oral mucosal diseases, as a physiopathological regulator [44]. Many recent studies have reported increased NO production in Table 3 certain temporomandibular disorders [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the inhibition of activity could be due to the NOmediated nitrosylation of receptors or other proteins involved in the secretion signal transduction pathways (Caulfield et al 2009). However, this relationship between increased nitrite concentrations and salivary gland hypofunction is more complicated, since other oral inflammatory disorders exhibit increased nitrite concentrations in saliva as well (Kendall et al 2000, ;Kendall, Marshall, and Bartold 2001, ;Ohashi, Iwase, and Nagumo 1999).…”
Section: Potential Roles Of No and Inos In Exocrine Hypofunctionmentioning
confidence: 99%
“…O aumento de nitrito quantificado na saliva foi encontrado em pacientes com recorrentes ulcerações orais aftosas. Observa-se um aumento do nível de iNOS gengival durante a inflamação periodontal, quando comparada com tecidos gengivais não inflamados 22 . Altas quantidades de L-arginina e L-citrulina em tecido gengival inflamado in vivo e a expressão de iNOS em macrófagos, linfócitos, e polimorfonucleares em periodontites induzidas experimentalmente em ratos, bem como em fibroblastos, células epiteliais, macrófagos e células endoteliais em periodontite humana, revelam a possível participação do NO na doença periodontal.…”
Section: Revisão Da Literaturaunclassified